Influência do hipoclorito de cálcio na adesão de materiais resinosos à câmara pulpar e ao canal radicular - Pauletto, Guilherme (2023)
This dissertation is composed of two studies. The first study aimed to compare the effect of sodium hypochlorite (NaOCl) and calcium hypochlorite [Ca(OCl)2], followers or not of the use of sodium thiosulfate (Na2S2O3), on the bond strength of a resin composite restoration to pulp chamber dentin. For this, the pulp chamber of fifty human molars were randomly distributed into 5 groups (n=10) according to the immersion protocol: 2.5% NaOCl; 2.5% NaOCl + 5% Na2S2O3; 2.5% Ca(OCl)2; 2.5% Ca(OCl)2 + 5% Na2S2O3; and 0.9% sodium chloride (NaCl), (control). Subsequently, the samples were restored with resin composite. Three sticks were obtained from the pulp chamber and subjected to the microtensile test. Scanning electron microscopy (SEM) and energy dispersive x-ray spectroscopy (EDS) analyzes were obtained from the pulp chamber roof (n=8) for mineral quantification. As a result, compared to control, the 2.5% NaOCl group was associated with the lowest values of bond strength and the 2.5% Ca(OCl)2 group presented similar bond strength. The 5% Na2S2O3 was able to increase the bond strength after the use of 2.5% NaOCl, but not after 2.5% Ca(OCl)2. The group treated only with 2.5% Ca(OCl)2 had a higher Ca/P ratio on the dentin surface. The second study aimed to evaluate the bond strength in the different dentinal thirds of the post space and adaptation failures (gaps) at the cement/dentin interface, resulting from the interaction between a dual-curing resin cement and a substrate irrigated with different concentrations of NaOCl or Ca(OCl)2. For this, after intraradicular preparation for posts in 50 endodontically treated premolars, the specimens were divided into 5 groups (n=10) according to the irrigant: 0.9% NaCl (control); 2.5% NaOCl; 5.25% NaOCl; 2.5% Ca(OCl)2; and 5.25% Ca(OCl)2. After irrigation, the posts were cemented with a dual-curing resin cement. One slice from each third were submitted to the push-out test. A additional slice of the middle third was submitted to confocal images for analysis of adaptation failures (gaps). As a result, the group treated with 5.25% NaOCl showed lower bond strength values than the control group. Bond strength decreased from coronal to apical in the post space. The 5.25% NaOCl generated more cohesive failures compared to the control group and 2.5% Ca(OCl)2. The groups treated with NaOCl had the highest percentages of gaps in relation to the control. Regardless of concentration, Ca(OCl)2 had no influence on the bond strength, and on the occurrence of gaps. In general conclusion, in both studies, Ca(OCl)2 did not affect bond strength in adhesive procedures. In addition, it was not affected by Na2S2O3, increased the Ca/P ratio on the dentin surface and did not interfere with the presence of gaps in the post space.